The effect of quality service and price upon the customers satisfaction (case study at TIKI branch at Jl. K. H. Sholeh Iskandar Bogor) - Adri Wihananto (STIE Binaniaga, 2019)
This research aims to study the effect of quality service and price either simulatenously or partially upon the customers satisfaction at PT TIKI Branch at Jl. K. H. Sholeh Iskandar Bogor. Analytical technique of this research has applied multiple linear regression analysis to figure out to which extent the quality service and price either simultaneously or partially has affected the customers satisfaction. The result has indicated that quality service and price simultaneously have affected significantly the customers satisfaction. This result has depicted that the value of F-count is 71.270 , however Ftable df: α, (k-1), (n-k) = 0.05, (2-1), (146-3) is 4.60 due to F-count > Ftable (71.270 > 4.60) and its sig.value of 0.000 < 5% (0.05). Keywords: Quality Service, Price, Customers Satisfaction